Effect of dietary formic acid as replacement of streptomycin on growth and nutrient digestibility in broiler (Bangladesh Journal of Animal Science, 2015)
An eight week feeding trial was carried out to compare the effect of antibiotic growth promoter (streptomycin) (AGP) and formic acid (FA) on growth and nutrient digestibility in broiler. A number of 150 day old (Hubbard strain) birds were allocated in 05 dietary groups viz. control, control with 0.02% AGP, control with 0.25% FA, control with 0.50% FA, control with 0.75% FA. Each group was replicated thrice having 10 birds and the birds were fed diet and water ad libitum for 8 weeks. Apparent digestibility of nutrients was determined at the end of the experiment. A significantly (p